Science Teachers’ Attitude regarding Use of Digital Tools in Public School of Punjab - Shafia Baber, Shahzada Qaisar (JSE, 2023)
Abstract Science teachers in many countries use Digital tools (DTs) less frequently, despite the increasing potential of DTs for teaching and learning. The attitude of science teachers toward DTs and their perceptions of DTs' use in the classroom has a significant effect on their use of ICT in their learning mand teaching activities. T